2010
DOI: 10.1037/a0018947
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of achievement goal measures: Different labels for the same constructs or different constructs with similar labels?

Abstract: This meta-analysis addresses whether achievement goal researchers are using different labels for the same constructs or putting the same labels on different constructs. We systematically examined whether conceptual and methodological differences in the measurement of achievement goals moderated achievement goal intercorrelations and relationships with outcomes. We reviewed 243 correlational studies of self-reported achievement goals comprising a total of 91,087 participants. The items used to measure achieveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

68
1,003
13
45

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,018 publications
(1,181 citation statements)
references
References 116 publications
68
1,003
13
45
Order By: Relevance
“…Correlations with these concepts are sufficiently different for the six goal constellations as to justify a multiple goal perspective. In specific, the correlational pattern of the Outcome Goal construct differs so much from those of the other three performance goals, that this supports the suggestion by Hulleman et al (2010) to position Outcome Goals in a separate category, somewhat in between learning and performance goals. Both correlational analysis and the analysis of gender differences suggest that the two normative goals, Normative Outcome and Normative Ability Goals, take rather unique positions, thereby rejecting the suggestion in the Grant and Dweck (2003) study to merge both constructs into one factor.…”
Section: Gender Differencessupporting
confidence: 69%
See 1 more Smart Citation
“…Correlations with these concepts are sufficiently different for the six goal constellations as to justify a multiple goal perspective. In specific, the correlational pattern of the Outcome Goal construct differs so much from those of the other three performance goals, that this supports the suggestion by Hulleman et al (2010) to position Outcome Goals in a separate category, somewhat in between learning and performance goals. Both correlational analysis and the analysis of gender differences suggest that the two normative goals, Normative Outcome and Normative Ability Goals, take rather unique positions, thereby rejecting the suggestion in the Grant and Dweck (2003) study to merge both constructs into one factor.…”
Section: Gender Differencessupporting
confidence: 69%
“…Recent debates on the nature of achievement goals (see e.g. Brophy (2005), Hulleman, Schrager, Bodmann, and Harackiewicz (2010), Senko, Hulleman, and Harackiewicz (2011)), directly impact this study. One issue in that debate is the issue of mastery goals versus the multiple goal perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has indicated that associations with goal orientation constructs differ depending on the measures employed and the sociodemographic characteristics of the sample. Measures of performance-approach goal orientation comprising mainly normatively-referenced measures have been found to be positively correlated with GPA whereas measures comprised mainly of appearance and evaluative items are negatively correlated (Hulleman, Schrager, Bodmann and Harackiewicz, 2010). We concur with Hulleman et al's call for greater theory-measurement consistency.…”
Section: Comparison With Previous Reviewsmentioning
confidence: 99%
“…A dimensão das crenças motivacionais foi baseada em trabalhos anteriores (Eccles & Wigfi eld, 2002;Hulleman et al, 2010), e é composta por 23 itens (α=0,89) distribuídos pelas seguintes subescalas: (a) Expectativas de autoefi cácia (e.g. "Acho que sou capaz de aprender as matérias da escola"; 4 itens; α=0,77); (b) Metas de realização -metas de aprendizagem (e.g.…”
Section: Instrumentounclassified
“…Wolters & Rosenthal, 2000). As expectativas que os alunos têm sobre a sua capacidade para regular o comportamento e realizar as tarefas escolares, em domínios específi cos -expectativas de autoefi cácia -infl uenciam as metas que os estudantes estabelecem para si, o seu nível de motivação e a persistência na realização das tarefas escolares (Eccles & Wigfi eld, 2002;Hulleman, Schrager, Bodman, & Harackiewicz, 2010). As metas de realização defi nem-se como representações cognitivas de um resultado futuro que um aluno pretende alcançar ou evitar.…”
unclassified